Instability mechanism of coal pillar in steeply dipping ultra-thick coal seam “segmented and stratified” combined mining - Yong LIU; Yao YANG; Xiao WANG; Wenqiang WANG; Xuesong WU; Anye CAO; Zujun LU; Tao YANG; Zhanquan WEI (Meikuang Anquan)
In order to solve the problems of frequent high energy microearthquakes and large roadway deformation in full-mechanized caving “segmented and stratified” combined mining in Yanbei Coal Mine with large dip angle and extra-thick coal seam, theoretical analysis, numerical simulation and field measurement are used to study the bearing stress characteristics of coal pillars and the instability mechanism of coal pillars. The load-bearing mechanical model of composite mining coal pillar is established, and the load-bearing stress distribution under the influence of coal pillar width is analyzed in three forms: asymmetric saddle shape, asymmetric platform shape and single peak shape, and it is determined that the load-bearing stress of coal pillar is more prone to instability when it is presented in asymmetric platform shape. The simulation results show that under the influence of pre-abutment pressure in inclined stratified mining, the section coal pillar is in a state of high stress, and the stress change rate is the most significant. The main cause of pillar instability is the local stress concentration in the combined mining of “segmented and stratified” coal seam with large dip angle; based on the instability mechanism of coal pillar in the composite mining area with large dip angle and ultra-thick coal seam, the prevention and control idea of rock burst of working face and key areas, the plan of the deep hole pre-splitting blasting in the roof and the combining of near and far blasting in the coal body, pressure relief in batches and shock absorption and shock prevention is formulated, which effectively reduces the stress and energy level of the gob side and significantly reduces the “segmented and stratified” composite mining of large dip angle and ultra-thick coal seam.